Eucalyptus growth and initial productivity in response to different sources of boron - Mageste, José Geraldo; Cordeiro Milagres, Vitor Augusto; Durães, Tânia Marta (International Journal of Advanced Engineering Research and Science, 2022)
Boron (B) deficiency in forest production systems has been reported in several eucalyptus species. The low biochemical cycling of B and the leaching losses justify the need for effort to get the fertilization of this nutrient right. In this context, the efficiency of three sources of boron with different solubilities was evaluated in a dystrophic Red Latosol, with a sandy loam texture, in eucalyptus crops at juvenile age. Ulexite (10% boron), boric acid (17,2%), and sodium tetraborate (15%) were evaluated, providing 800 g ha-1 of B. For comparison, a control without boron was used, totaling four treatments in a randomized block design. To evaluate growth and productivity, total height (Ht) and diameter at breast height (DBH) were analyzed at 12 months, in addition to analysis of plant tissue at the end of this period. There was an influence of borate fertilization on the initial growth of eucalyptus (Clone I 144). Although there was no interaction between the sources of boron in the development of the initial dendrometric attributes, there was variation between the sources in relation to the concentration of boron in the plant tissue.